Highly bright perovskite light-emitting diodes enabled by retarded Auger recombination - Zhiqi Li; Qi Wei; Yu Wang; Cong Tao; Yatao Zou; Xiaowang Liu; Ziwei Li; Zhongbin Wu; Mingjie Li; Wenbin Guo; Gang Li; Weidong Xu; et al. (Nature Communications)
Abstract One of the key advantages of perovskite light-emitting diodes (PeLEDs) is their potential to achieve high performance at much higher current densities compared to conventional solution-processed emitters. However, state-of-the-art PeLEDs have not yet reached this potential, often suffering from severe current-efficiency roll-off under intensive electrical excitations. Here, we demonstrate bright PeLEDs, with a peak radiance of 2409 W sr−1 m−2 and negligible current-efficiency roll-off, maintaining high external quantum efficiency over 20% even at current densities as high as 2270 mA cm−2. This significant improvement is achieved through the incorporation of electron-withdrawing trifluoroacetate anions into three-dimensional perovskite emitters, resulting in retarded Auger recombination due to a decoupled electron-hole wavefunction. Trifluoroacetate anions can additionally alter the crystallization dynamics and inhibit halide migration, facilitating charge injection balance and improving the tolerance of perovskites under high voltages. Our findings shed light on a promising future for perovskite emitters in high-power light-emitting applications, including laser diodes.